Development of technology for obtaining and formulating high-protein potato food products with a low glycemic index - V. V. Shilov; V. V. Litvyak; A. A. Zhurnya; Yu. F. Roslyakov; T. V. Okulova; A. M. Mazur (Новые технологии, 2025)
Introduction. Properly organized preventive and dietary nutrition is an important component of the preventive approach to protecting human health.The goal of the research was to create balanced recipes for high-protein potato food products (potato pancakes and dumplings) with an optimized glycemic index (GI) based on mathematical modeling.The research. The technology for obtaining highprotein potato food products, such as pancakes and dumplings, with a reduced GI has been developed in the research. The research takes into account the growing problems with insufficient protein intake in the diet, and focuses on the need to develop new functional foods that can meet the needs of the modern population.The methods. Mathematical modeling was used to create balanced recipes for high-protein potato products. To assess the taste and texture characteristics, organoleptic methods, as well as physicochemical methods of analysis to determine the content of protein, fat and carbohydrates were used. GI was analyzed on a group of healthy volunteers, which made it possible to assess the effect of various recipes on blood sugar levels.The results. High-protein potato pancakes and dumplings recipes containing both animal and vegetable proteins have been developed. Experimental data indicate that the protein content in the developed products is at least 20% of the total caloric value. GI measurements confirm that freezing to -18°C contribute to a GI reduction of 28.6% on average, making these products more acceptable for people monitoring their blood sugar levels.The conclusion. High-protein potato products can be recommended as functional products for preventive and therapeutic nutrition, as well as for athletes and people leading an active lifestyle. The study emphasizes the importance of protein in the diet for maintaining health, improving performance, and preventing metabolic diseases. The development of such products can contribute to improving the quality of nutrition and health of the population, which is especially important in modern conditions.